Accessibility as a conditioning factor in treatment for exudative age-related macular degeneration - Real, Juan Pablo (2013)
Purpose: Ranibizumab and bevacizumab coexist as the main therapeutic strategies for the treatment of neovascular age-related macular degeneration (NV-AMD). In Argentina, the access pathways to the drugs are different. Patients with different pathways and gatekeepers to access may experience different outcomes. The purpose of this work was to estimate the impact on therapeutic effects and visual outcome of the different accessibilities to NV-AMD treatment.  Methods: A retrospective analysis of the charts of 78 patients with previously untreated exudative AMD, who were treated with ranibizumab or bevacizumab between January 2009 and December 2011, was conducted. The main outcomes measured included time delay and change in mean best-corrected visual acuity (BCVA) between diagnosis and treatment and mean BCVA change at 1-year follow-ups. Results: The delay between diagnosis and treatment and decrease in visual acuity over this time was significantly higher for patients treated with ranibizumab. At 1 year after the initiation of treatment, BCVA had a mean increase from baseline of 0.11 letters in the bevacizumab group with a mean of 4.71 injections, compared with a decrease of 8.87 letters with a mean of 2.98 injections in the ranibizumab group. Conclusions: Access to treatment can be a key factor for success of therapy. Waiting times and availability of doses are crucial in the treatment of NV-AMD. Solving the problems related to delayed initiation of therapy and the difficulties in the maintenance phase are more important than define whether bevacizumab or ranibizumab is used.